Liquid Biopsy beyond Cancer: A miRNA Detection in Serum with Electrochemical Chip for Non‐Invasive Coeliac Disease Diagnosis. Issue 9 (3rd July 2022) - Caratelli, Veronica; Moccia, Maria; Paggioro, Francesca R.; Fiore, Luca; Avitabile, Concetta; Saviano, Michele; Imbriani, Anna Lisa; Dardano, Principia; De Stefano, Luca; Moscone, Danila; Colabufo, Nicola A.; Ghafir El Idrissi, Imane; et al.
Abstract : Coeliac disease is a very common autoimmune disease estimated to affect 1 in 100 people worldwide. It occurs in genetically predisposed people where the ingestion of gluten leads to damage in the small intestine, and it is accurately diagnosticated through duodenal biopsy, an invasive diagnostic method. The liquid biopsy, generally used for monitoring cancer, is an appealing alternative even for autoimmune pathology such as coeliac disease, allowing for detecting disease progression or resistance to treatment. For this reason, an electrochemical peptide nucleic acid (PNA) device combined with a smartphone‐assisted potentiostat for non‐invasive coeliac disease diagnosis is proposed, by measuring the selected overexpressed miRNA‐486‐5p in serum, enlarging the application of liquid biopsy in nontumor pathologies. For highly sensitive detection, the polyester‐based printed sensor is nanomodified with gold nanoparticles and a synthetic customized PNA probe. The designed sensor can detect the target analyte in the range of 10–100 nm with a limit of detection of 0.7 nm by measuring the variation of the response of the electrochemical mediator hexaammineruthenium in the presence of PNA–miRNA duplex on the nanostructured working electrode surface. The analyses testing serum samples are found in agreement with ones obtained by real‐time quantitative polymerase chain reaction (RT‐qPCR), demonstrating the reliability of this innovative electrochemical chip developed. Abstract : Herein, a non‐invasive diagnostic device is developed for the detection of miRNA‐486‐5p, which expression resulted to be highly specific for the coeliac condition. Using a smartphone‐assisted potentiostat, the peptide nucleic acid (PNA)‐based electrochemical chip can detect the miRNA target in 60 min both in standard solution than in serum samples with a limit of detection equal to 0.5 and 0.7 nm, respectively.